(untitled) (Journal of Universal Science Research, 2025)
This article focuses on a comprehensive analysis of the semantic and functional features of football-related lexical units in the English language. It provides an examination of football terminology through the lens of linguistic theories such as semantic field theory, prototype theory, and communicative-functional approach. The terms are categorized based on their semantic, morphological, and contextual properties, with real-life examples analyzed for each type. Findings suggest that football terminology is a significant area of study in both linguistics and translation studies.